Diagnosis of oral potentially malignant disorders: Overview and experience in Oceania - Rich, Alison M.; Hussaini, Haizal M.; Nizar, Muhammad Aiman Mohd; Gavidi, Ratu Osea; Tauati-Williams, Elizabeth; Yakin, Muhammed; Seo, Benedict (Frontiers in Oral Health, 2023)
The diagnosis and management of oral potentially malignant disorders (OPMD) should be the same the world over, but there are important nuances in incidence, aetiological factors and management opportunities may lead to differences based on ethnogeography. In this review we update and discuss current international trends in the classification and diagnosis of OPMD with reference to our experience in various regions in Oceania. Oceania includes the islands of Australia, Melanesia (including Papua New Guinea, Fiji, Solomon Islands, Micronesia and Polynesia (including New Zealand, Samoa, Tonga) and hence has diverse populations with very different cultures and a range from well-resourced high-population density cities to remote villages.